Analysis the performance of adaptive demodulator in terms of bit error rate for software defined radio - Bakhraiba, Ahmed Mohamed Salih; Khatun, Sabira; Noordin, Nor Kamariah; Ismail, Alyani; Mohd Ali, Borhanuddin (2009)
Nowadays, a lot of effort have been given to reduce hardware and software development cost. Many of today's military and commercial communication systems use Software Defined Radio (SDR) has been one of the new techniques developed to change the way the traditional wireless communication system work. Through the definition of the SDR, this paper is aimed to designing an adaptive system to automatically demodulating the modulated signal after identifying the modulation type of the signal using digital signal processing techniques. The demodulation process has been investigated using the bit error rate (BER). The SIMULINK tool was used as the simulation software throughout this paper. The BER results for the demodulation process showed that at 15dB the error rate is less than the rate at low SNR.